Clinical Characteristics, Mortality and Associated risk factors in COVID-19 patients reported in ten major hospitals of Khyber Pakhtunkhwa, Pakistan - UlHaq, Zia; Shahzad, Muhammad; Khattak, Maria Ishaq; Fazid, Sheraz; Ullah, Naeem; Sherin, Akhtar; Ulhaq, Naeem; Izhar, Asif; Farooq, Umer; Darwesh, Nizam Muhammad; et al. (Journal of Ayub Medical College Abbottabad, 2021)
Background: COVID-19 is an ongoing public health issue across the world. Several risk factors associated with mortality in COVID-19 have been reported. The present study aims to describe clinical and epidemiological characteristics and predictors of mortality in hospitalized patients from Khyber Pakhtunkhwa, a province in Pakistan with highest COVID-19 associated case fatality rate. Methods: This multicentre, retrospective study was conducted in hospitalized COVID-19 patients who died or discharged alive until 1st May 2020. Data about sociodemographic characteristics, clinical and laboratory findings, treatment and outcome were obtained from hospital records and compared between survivors and non-survivors. Statistical tests were applied to determine the risk factors associated with mortality in hospitalized patients. Results: Of the total 179 patients from the 10 designated hospitals, 127 (70.9%) were discharged alive while 52 (29.1%) died in the hospital. Overall, 109 (60.9%) patients had an underlying comorbidity with hypertension being the commonest. Multivariate logistics regression analysis showed significantly higher odds of in-hospital death from COVID-19 in patients with multiple morbidities (OR 3.2, 95% CI 1.1, 9.1, p-value=0.03), length of hospital stay (OR 0.8, 95% CI 0.7, 0.9, p-value <0.001), those presenting with dyspnoea (OR 4.0, 95% CI 1.1, 14.0, p-value=0.03) and oxygen saturation below 90 (OR 9.6, 95% CI: 3.1, 29.2, p-value <0.001). Conclusion: Comorbidity, oxygen saturation and dyspnoea on arrival and length of stay in hospital (late admission) are associated with COVID-19 mortality. The demographic, clinical and lab characteristics could potentially help clinician and policy makers before potential second wave in the country. Keywords: COVID-19; Clinical Characteristics; Mortality; Khyber Pakhtunkhwa; Pakistan